Inspiring Women into Technology: the EUD Megacommunity - Irene Kamberidou (Proceedings of the 5th International Conference on Interdisciplinarity in Education ICIE’10: New Higher Education Programs & Jointly 4th International Steering Committee Meeting, June 17_19, 2010, Tallinn, Estonia, 2010)
Kamberidou, I. (2010). “Inspiring Women into Technology: the EUD Megacommunity”. Poster presentation in proceedings of the 5th International Conference on Interdisciplinarity in Education ICIE’10: New Higher Education Programs & Jointly 4th International Steering Committee Meeting, June 17_19, 2010, Tallinn, Estonia. [Also see article in: http://ec.europa.eu/information_society/events/cf/daa11/person.cfm?personid=21537 ABSTRACT: In order to promote the targets of the European Center for Women and Technology (ECWT) and increase the number of girls and women in the knowledge based economy until the year 2020, the ECWT has developed the European Directory (EUD) of Women and ICT (http:// www.ictwomendirectory.eu), an online directory, an ecospace, a meeting point for ICT women in Europe. The EUD, created with the support of the European Commission DG Information Society and Media, was launched in Brussels in October 2009 by Commissioner Viviane Reding.[1] (Kamberidou 2010) Specifically, on the 8th of October 2009, Commissioner Reding welcomed 32 new signatories of the Code of Best Practices for Women and ICT and introduced this new tool –the online Directory for Women in ICT: http://www.ictwomendirectory.eu.  Specifically, this prentation showcases, or rather introduces a new ecospace, an online directory, a tool for getting more girls and women into the technology sector. It is the first regional directory for Women and ICT issues, a meeting point for ICT women in Europe and a megacommunity for  innovative collaboration in the Women and ICT and related sectors.   Keywords: new ecospace, megacommunity, collaboration platform, European level database, Web Community for Women in ICT.